Impact of relationship marketing on short-stay hotel guest loyalty - Ccorisapra-Quintana, Jeferson (2022)
This manuscript aims to examine the effect of relationship marketing on short-stay hotel guest loyalty. A quantitative, explanatory level and ex post facto design were was used. The study was executed in the city of Ayacucho and involved the participation of 225 tourists who had more than three experiences in the hotels. The information was collected by means of an online questionnaire and a self-administered survey. The data were processed in SPSS 27.0 statistician by applying bivariate correlations and multiple linear regression. The main result points out that relationship marketing positively impacts short-stay hotel guest loyalty with an estimate (R2=0.362). Likewise, the components of relationship marketing, trust (β=0.238; sig.<0.001), commitment (β=0.186; sig.<0.006), communication (β=0.180; sig.<0.006) and conflict management (β=0.199; sig.<0.002) also found a positive influence on guest loyalty.